NAVIGATING THE COMPLEXITIES IN HUMAN RESOURCE MANAGEMENT IN THE SHARING ECONOMY - Kaur, Harpreet (PROFESSIONAL STUDIES: Theory And Practice, 2026)
The term Sharing economy describes a labour market where jobs are offered by companies, outside parties, or online platforms and are either project-based or based on fixed-term contracts. This economic model has fundamentally changed workplaces, altering how people work and how the economy runs. The number of Sharing workers is projected to rise further as a consequence of many talented people choosing Sharing work as their main source of income due to its unparalleled advantages. The obstacles in human resources brought about by the changing Sharing economy are examined in this article. It looks at how hiring practices, legal compliance, and performance indicators are affected by the Sharing economy and provides organizations with tactical suggestions. These observations are meant to assist companies in managing Sharing workers efficiently and guaranteeing their smooth assimilation into the workforce. In order to assess the function of HRM in the Sharing economy, a thorough mixed-method approach was carefully used, combining quantitative and qualitative techniques. 200 HR professionals from a variety of industries were given a structured survey as part of the quantitative component, which had an astounding 75% response rate (150 respondents). HRM procedures like hiring (30%), performance management (25%), training (20%), and development (25%), were the main topics of the survey. Simultaneously, 40 Sharing workers from various industries participated in qualitative semi-structured interviews, which constituted a 10% sampling of the entire survey participant pool. For quantitative analysis, the study used SPSS software, concentrating on factor analysis and multiple regression methods. In accordance to the quantitative analysis, 54% of HR professionals highlighted performance management systems modified for short-term contracts, and 68% of HR professionals reported using flexible recruitment strategies catered to Sharing workers. Only 45% and 38% of respondents, respectively, indicated that training and development were specifically addressed for Sharing workers. These results were further clarified by qualitative interviews, which revealed that Sharing workers strongly preferred transparent performance management systems (65%) and more inclusive training opportunities (70% of interviewees). A discrepancy between HRM practices and Sharing worker expectations was indicated by the fact that 60% of Sharing workers cited the need for development pathways that could result in longer-term employment or improved skills.